Pentingnya Kegiatan Barzanji Untuk Mengembangkan Nilai-Nilai Pendidikan Akhlak Di Pondok Pesantren - Warman, Adithiya; Zakiyatinnisa, Wafdah (An-Nuha, 2025)
This study aims to analyze the role of Barzanji activities in developing moral education values among students at Pondok Pesantren Asshiddiqiyah 06 Serpong, focusing on forming personal and social ethics. The study identifies aspects of religious activities that contribute to students' character development. One unique feature of the Barzanji activities at this Islamic boarding school is the use of hadroh musical instruments to accompany the recitation of Al-Barzanji verses, which enhances students' enthusiasm and fosters their religious spirit. This research employs a qualitative approach with a case study design. Data were collected through observation, in-depth interviews, and documentation, and analyzed using data reduction, data presentation, and conclusion-drawing techniques. Data validity was ensured through source and method triangulation. The findings indicate that Barzanji activities positively impact students' morals in two main aspects. First, on an individual level, these activities shape personal ethics such as honesty (shidiq), and trustworthiness (amanah), and enhance harmonious relationships within the family. Second, on a social level, Barzanji activities encourage active participation in religious events and the application of Islamic social values in daily life. The study concludes that Barzanji activities not only serve as religious traditions but also play a significant role in shaping students' character both individually and socially. The practical implication of this research highlights the importance of integrating religious activities into the moral education curriculum at Islamic boarding schools to strengthen the character of the younger generation.